2004
DOI: 10.3141/1883-19
|View full text |Cite
|
Sign up to set email alerts
|

Automobile Drivers' Perceptions of Service Quality on Urban Streets

Abstract: The Highway Capacity and Quality of Service Committee of TRB, which oversees the development of the Highway Capacity Manual, has formally recognized a need to improve the current level-of-service (LOS) methodologies. Among the concerns about the methodologies is the extent to which LOS estimates correspond to road users' perceptions. In recognition of these concerns, the objectives of this study were to ( a) develop and test a methodology to obtain drivers' opinions with regard to urban street quality of servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 3 publications
0
22
0
3
Order By: Relevance
“…If there is a need to investigate service quality perceived by a wider driving population, a survey method may be best. Table 1 shows the strengths and weaknesses of each method as indicated in previous studies (13,14).…”
Section: Methodsmentioning
confidence: 99%
“…If there is a need to investigate service quality perceived by a wider driving population, a survey method may be best. Table 1 shows the strengths and weaknesses of each method as indicated in previous studies (13,14).…”
Section: Methodsmentioning
confidence: 99%
“…One study found that motorists did not perceive six-scales of delay (A-F), but instead thought in terms of three: ''good, '' ''marginal,'' and ''poor'' (Fang et al, 2003). Other studies conclude that motorist perception of the quality of an intersection is highly variable and influenced by trees, aesthetics of the surroundings, the size of other vehicles such as SUVs and pick-up trucks, pavement quality, and aggressive driving (Flannery et al, 2006;Ko et al, 2006;Lee et al, 2007;Pecheux et al, 2004).…”
Section: Los and Urban Spacementioning
confidence: 97%
“…Unlike the ND policy, the TS policy allows a government agency to consider the drivers' and carriers' priorities such as drivers' preference to avoid the road which has a high risk, and carrier companies try to achieve more profit by choosing the least cost path that reduces an operational cost (Pécheux et al 2004), simultaneously. Recently, Wang et al (2011) suggested a dual toll pricing framework to control both regular and hazmat traffic flows for the public safety since hazmat carriers are not only a part of the hazmat traffic flows, but also belong to, and cannot be separated from the regular traffic flows.…”
Section: Kim Mungle and Sonmentioning
confidence: 98%